Tied with Hair Strands- A Case of Hair Tourniquet Syndrome involving Labia Minora in an Adult Woman from Nepal - Shrestha, Deepak; Gupta , Swati; Singh, Kritina; Aryal , Shreyashi (Journal of Nepal Health Research Council, 2021)
Hair tourniquet syndrome is the strangulation of body appendages by a thread of hair. If neglected, it results in lymphatic obliteration, venous congestion, and arterial obstruction. A 25 years lady with a history of insect bite presented with intense itching and painful swelling in the left labia minora for three days. She had tied the swollen part with a bunch of hair strands leading to painful swelling. Local inspection revealed a 2x2 cm swelling in the left labia minora. The tourniquet effect was released by cutting the hair. Hair tourniquet syndrome involving female genitalia requires immediate recognition and treatment. Keywords: Hair tourniquet syndrome; hair-thread tourniquet syndrome; labia minora